Effect of Gibberellic Acid (Gas) and Pre-chilling on Germination per cent of Nothofagus obliqua (mirb.) Oerst. and N. Procera Oerst. Seeds - Shafiq, Y. (Indian Forester, 1980)
Soaking Nothofogus obliqua Mirb. and N. procera Oerst seeds in 50, 100, 150 and 200 ppm GA3 solution for 24 hours had a highly significant effect on rate and percentage of germination; it decreased the germination period to 8-14 days and 6-10 days instead of 28 days, reapectively.Pre-chilling N. obliqua and N. procera for different intervals significantly increased rate and percentage or germination and decreased the period of germination to 8-14 days only with N. proecra.Combinations of treatment had a highly significant effect on germination rate and percentage for both species. The belt combinations for N. obliqua were 100, 150 and 200 ppm GA3, with 14 and 42 days pre-chilling, while the best combination for N. procera were 150 ppm with 7 days pre-chilling and 200 ppm with 14 days pre-chilling.